Remote ischemic preconditioning improves cognitive control in healthy adults: Evidence from an event-related potential study - Li, Yaling; Huang, Pei; Huang, Jun; Zhong, Zhifeng; Zhou, Simin; Dong, Huaping; Xie, Jiaxin; Wu, Yu; Li, Peng (Frontiers in Neuroscience, 2022)
It is suggested that remote ischemic preconditioning (RIPC) may be a promising treatment for improving healthy adults’ cognitive control. However, direct empirical evidence was absent. Therefore, this study aims to provide evidence for the impact of RIPC on cognitive control. Sixty healthy young male volunteers were recruited, and 30 of them received one-week RIPC treatment (RIPC group), while the rest didn’t receive RIPC (control group). Their cognitive control before and after RIPC treatment was evaluated using the classic Stroop task, and the scalp electricity activity was recorded by event-related potentials (ERPs). The behavioral results showed a conventional Stroop interference effect of both reaction times (RTs) and the accuracy rate (ACC), but the Stroop interference effect of RTs significantly decreased in the posttest compared to the pretest. Furthermore, at the electrophysiological level, ERP data showed that N450 and SP for incongruent trials were larger than that for congruent trials. Importantly, the SP differential amplitude increased after RIPC treatment, whereas there was no significant change in the control group. These results implied that RIPC treatment could improve cognitive control, especially conflict resolving in the Stroop task.